THE CORRELATION BETWEEN SELF AFFICACY AND STUDENTS’ READING COMPREHENSION OF SECOND GRADE STUDENTS AT SMA NEGERI 2 WAWOTOBI - Asri Nofa Rama (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2022)
This research aimed to know the correlation between students’ self-efficacy and their reading comprehension at SMA N 2 Wawotobi. This research used correlative research design. The researcher conducted this research in SMAN 2 Wawotobi. The population of this research that consisted of four classes with the number of populations was 129 students. Since the number of populations was large, the researched used simple random sampling technique. The number of of sample of this research was 32 science students. A questionnaire was used to measure students’ reading self-efficacy and a reading test was conducted to know students’ reading comprehension. The collected data then the researcher analyzed by using the correlational analysis computerized with SPSS 24. Based on the analysis results used Pearson product-moment correlation, it was found that there was statistically significant positive correlation between self-efficacy and reading comprehension in p-output was 0.002 which was smaller than 0.05 (0.002<0.05). Besides, the correlational coefficient of the test was .537. Thus, the level of correlation was moderate.